Problem wsparcia finansowego dla zrównoważonego rozwoju w rolnictwie - Baum, Rafał (The problem of financial support for sustainable development in agriculture, 2007)
In this paper, based on break even point analysis, was presented the methodical elaboration of the fmancial support question for sustainable development of agriculture. It was defined generał manner of calculating the payments (compensations for farmers) for service of over average services in favour of society and natural environments. It was indicated simultaneously on many problems, which appear by reason of introduction fmancial instruments mentioned earlier.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 378-384